2014
DOI: 10.1371/journal.pone.0098981
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Inhibits Behavioral Sensitization by Blocking Methamphetamine-Induced MAPK Pathway Activation in the Caudate Putamen in Mice

Abstract: GoalTo investigate the effect of luteolin on methamphetamine (MA)-induced behavioral sensitization and mitogen-activated protein kinase (MAPK) signal transduction pathway activation in mice.MethodsMice received a single dose of MA to induce hyperactivity or repeated intermittent intraperitoneal injections of MA to establish an MA-induced behavioral sensitization mouse model. The effect of luteolin on the development and expression of MA-induced hyperactivity and behavioral sensitization was examined. The expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Adaptations in the CPu has been associated with methamphetamine sensitization (Li et al 2016a; Li et al 2016b; Yan et al 2014). However, the subdivisions of the striatum have important functional differences that need to be considered (Boekhoudt et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptations in the CPu has been associated with methamphetamine sensitization (Li et al 2016a; Li et al 2016b; Yan et al 2014). However, the subdivisions of the striatum have important functional differences that need to be considered (Boekhoudt et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Yan et al (2014) demonstrated that the casein kinase 2-inhibitor luteolin inhibited behavioral sensitization by blocking methamphetamine-induced MAPK activation in the caudate putamen of mice. Given the similar observations from the present study, we propose a potential beneficial effect of ibudilast to attenuate methamphetamine-seeking during abstinence by reversing the levels the synaptic protein PEBP1.…”
Section: Discussionmentioning
confidence: 99%
“…METH challenge after withdrawal from repeated METH exposure has been shown to induce behavioral sensitization related to pERK induction in both CPu and NAc as well as ΔFosB expression in the CPu 122,169,170 . The development and expression of METH behavioral sensitization and challenge-augmented pERK induction were inhibited by levo-tetrahydropalmatine, an antagonist of D1- and D2-Rs 169,171,172 , suggesting the involvement of DA receptors in chronic METH-induced pERK and behavioral sensitization.…”
Section: Erk Signaling and Drug Addictionmentioning
confidence: 99%